1996
DOI: 10.1126/science.273.5279.1239
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Farnesyl Transferase Involved in Abscisic Acid Signal Transduction in Arabidopsis

Abstract: The hormone abscisic acid (ABA) modulates a variety of developmental processes and responses to environmental stress in higher plants. A collection of mutations, designated era, in Arabidopsis thaliana that confer an enhanced response to exogenous ABA includes mutations in the Era1 gene, which encodes the beta subunit of a protein farnesyl transferase. In yeast and mammalian systems, farnesyl transferases modify several signal transduction proteins for membrane localization. The era1 mutants suggest that a neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
337
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 396 publications
(353 citation statements)
references
References 15 publications
(1 reference statement)
9
337
0
7
Order By: Relevance
“…Germination assays in Arabidopsis are often performed in light on seeds freshly harvested or stored for a limited time (Léon-Kloosterziel et al, 1996a). Other parameters are the germination rate after different periods of cold treatment (Cutler et al, 1996) and germination in darkness (Meng et al, 2008; Kim et al, 2008). In addition to testing mature seeds, germination of immature seeds, either excised from the silique or within fruits detached from the plant, can be used to investigate genetic variation during the early stages of seed development (Raz et al, 2001).…”
Section: Of 18 the Arabidopsis Bookmentioning
confidence: 99%
See 1 more Smart Citation
“…Germination assays in Arabidopsis are often performed in light on seeds freshly harvested or stored for a limited time (Léon-Kloosterziel et al, 1996a). Other parameters are the germination rate after different periods of cold treatment (Cutler et al, 1996) and germination in darkness (Meng et al, 2008; Kim et al, 2008). In addition to testing mature seeds, germination of immature seeds, either excised from the silique or within fruits detached from the plant, can be used to investigate genetic variation during the early stages of seed development (Raz et al, 2001).…”
Section: Of 18 the Arabidopsis Bookmentioning
confidence: 99%
“…However most of ABA receptor genes were identified using reverse genetics in which screening for germination characteristics were performed that often showed no or small effects on ABA sensitivity for germination and dormancy it self was often not tested (reviewed in Holdsworth et al, 2008a). Forward screens for mutants in which seed germination is prevented by low concentrations of ABA that ordinarily permit germination of the wildtype seed were first described by Cutler et al (1996) resulting in the era1 (enhanced response to ABA) to era3 mutants. Subsequently using similar screens identified many additional loci that are involved in removal of sensitivity to ABA function, that when mutated lead to ABA hypersensitivity of imbibed after-ripened or moist-chilled seeds (Hugouvieux et al, 2001;Xiong et al, 2001;Nishimura et al, 2004; Katagiri et al, 2005;Zhang et al, 2005;Pandey et al, 2006;Saez et al, 2006;Yoine et al, 2006;Nishimura et al, 2007).…”
Section: Genes and Factors Affected In Seed Dormancy/germinationmentioning
confidence: 99%
“…hormone regulates, such as germination, growth retardation or other stress responses leading to tolerance. Although these responses probably do not use the same set of signalling components, ABA sensitivity at germination for instance was found to be associated with enhanced drought tolerance in a number of cases (Cutler et al, 1996;Hugouvieux et al, 2001;Papp et al, 2004). Measuring retardation of root elongation at the seedling stage is a relatively simple way to characterize responsiveness to exogenously applied ABA (Thole et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Protein prenylation is a conserved function in fungi, plants, and animals (Maurer-Stroh, Washietl, & Eisenhaber, 2003;Yalovsky, Rodr Guez-Concepcion, & Gruissem, 1999). ABA hypersensitivity has been demonstrated in the era1 mutant Arabidopsis plants, which present a disruption of the encoding and correct formation of the PFT β-subunit (Cutler et al, 1996;Running et al, 2004). Due to the nature of the α-subunit being involved in the activity of both PFT and PGGT, it has been hypothesized the plp mutants should exhibit even more severe ABA hypersensivity than the era1 mutants (Running et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…ABA causes a myriad of responses to enhance survivability to stress conditions, including reducing water loss via closure of stomata (the leaf openings that let in carbon dioxide). Mutant lines of certain plant species have been identified that present ABA hypersensitivity, and demonstrate diminished seed yield and enhanced stomatal closure (Cutler, Ghassemian, Bonetta, Cooney, & McCourt, 1996;Pei, Ghassemian, Kwak, McCourt, & Schroeder, 1998;Running et al, 2004).…”
Section: Introductionmentioning
confidence: 99%